2008
DOI: 10.1128/jb.01416-07
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of an Acinetobacter baumannii Biofilm-Associated Protein

Abstract: We have identified a homologue to the staphylococcal biofilm-associated protein (Bap) in a bloodstream isolate of Acinetobacter baumannii. The fully sequenced open reading frame is 25,863 bp and encodes a protein with a predicted molecular mass of 854 kDa. Analysis of the nucleotide sequence reveals a repetitive structure consistent with bacterial cell surface adhesins. Bap-specific monoclonal antibody (MAb) 6E3 was generated to an epitope conserved among 41% of A. baumannii strains isolated during a recent ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
228
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(236 citation statements)
references
References 48 publications
5
228
0
3
Order By: Relevance
“…Loehfelm et al (6) identified a staphylococcal homologue of biofilm-associated protein (Bap), and after generating a transposon-mediated bap mutant in a contemporary A. baumannii clinical strain (307-0294), it was shown that the mutant produced \50% of the biofilm thickness produced by the parent strain. Bap is a surface exposed protein and, rather than being involved in bacterial cell attachment, appears to be important in maintaining mature biofilm architecture (6). Interestingly, antibodies directed to Bap bound to 93% of the four most common strain types from a clinical outbreak, as determined by MLST, whereas they bound to only 28% of the 35 less common strain types (6).…”
Section: Biofilm Formation and Use Of In Vitro Abiotic Models To Studmentioning
confidence: 99%
See 2 more Smart Citations
“…Loehfelm et al (6) identified a staphylococcal homologue of biofilm-associated protein (Bap), and after generating a transposon-mediated bap mutant in a contemporary A. baumannii clinical strain (307-0294), it was shown that the mutant produced \50% of the biofilm thickness produced by the parent strain. Bap is a surface exposed protein and, rather than being involved in bacterial cell attachment, appears to be important in maintaining mature biofilm architecture (6). Interestingly, antibodies directed to Bap bound to 93% of the four most common strain types from a clinical outbreak, as determined by MLST, whereas they bound to only 28% of the 35 less common strain types (6).…”
Section: Biofilm Formation and Use Of In Vitro Abiotic Models To Studmentioning
confidence: 99%
“…Bap is a surface exposed protein and, rather than being involved in bacterial cell attachment, appears to be important in maintaining mature biofilm architecture (6). Interestingly, antibodies directed to Bap bound to 93% of the four most common strain types from a clinical outbreak, as determined by MLST, whereas they bound to only 28% of the 35 less common strain types (6). The significance of this observation is unclear, but further research into the clinical importance of Bap in A. baumannii is clearly warranted.…”
Section: Biofilm Formation and Use Of In Vitro Abiotic Models To Studmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression level of csu operon is regulated by the two-component system -BfmS/BfmR, comprising a sensor kinase and a response regulator [39]. Biofilm-associated protein (Bap), expressed on the surface of the bacterial cells, is implicated in cell-to-cell adhesion providing biofilm development and maturation on different substrata [40]. Furthermore, one of the most important components of exopolysaccharides constituting biofilm matrix was polysaccharide polymer poly--beta-1,6-N-acetylglucosamine (PNAG) that is crucial for maintaining the integrity of A. baumannii biofilm under nutrient limitation and other environmental stresses [41].…”
Section: Virulence Factorsmentioning
confidence: 99%
“…This kit provides a two dye fluorescence assay based on membrane integrity with extensive use in various microorganisms in the literature as Acinetobacter baumanni (Loehfelm et al, 2008), Mycoplasma putrefaciens (McAuliffe et al, 2006), Escherichia coli, and Micrococcus luteus (Ali et al, 2018). In Figure 3, it is possible to observe the visualization of the microorganisms with the kit which allows to distinguish between live and dead (Loehfelm et al, 2008;McAuliffe et al, 2006;Ali et al, 2018).…”
Section: Visualization Of Membrane Damage Of Prokaryotes By Fluorescementioning
confidence: 99%